마이봄샘 기능 이상 환자에서 자동 온열 압박 치료기기의 임상적 효과 및 예후 분석 - 남승완(Seung Wan Nam); 임동희(Dong Hui Lim); 현주(Joo Hyun); 정태영(Tae Young Chung) (Daihan angwa haghoi jabji, 2016)
목적: 마이봄샘 기능 이상 환자에서 자동 온열 압박 치료기기(KCL 1100®, Korea KCL, Bucheon, Korea)의 효과 및 안전성 평가를 시행하고, 자동 온열 압박 치료 효과에 영향을 주는 요인을 알아보고자 하였다. 대상과 방법: 마이봄샘 기능 이상으로 진단된 환자 24명 48안을 대상으로 1달간 전향적 연구를 시행하였다. 대상 환자는 매일 하루 2회, 15분씩 자동 온열 압박 치료기기(KCL 1100®)를 사용하였고, 치료 전, 치료 2주 후 및 1달 후 내원하여 나안시력, 안압, Standard Patient Evaluation for Eye Dryness (SPEED), Ocular Surface Disease Index (OSDI), Lipid Layer Thickness (LLT), Meibomian Gland Secretion score (MGS), Meibomian Gland Expressibility (MGE), 눈물막 파괴 시간(tear break-up time, BUT), 플루오레신각막 염색 점수(Oxford scale)를 측정하였다. 자동 온열 압박 치료의 효과 및 안전성 분석 시 내원 시마다 측정한 각각의 지표를 짝지은 t 검정을 시행하였다. 자동 온열 압박 치료 효과에 영향을 주는 초기 요인을 확인하기 위해 이 지표들의 치료 전과 치료 1달간 변화량에 대해 단일 회귀 분석을 시행하였다. 자동 온열 압박 치료에 따른 마이봄샘 기능 변화와 증상 호전 및 안구표면 변화의 관계를 확인하기 위해 치료 1달간 마이봄샘 기능의 변화량과 치료 1달간 건조증 증상 및 안구 표면 지표들의 변화량에 대해 단일 회귀분석을 시행하였다. 결과: 대상 환자들은 중등도 이하의 마이봄샘 기능 이상 환자로 치료 전 MGE의 평균은 3.08 ± 1.77, MGS의 평균은 4.11 ± 3.05였다. 자동 온열 압박 치료 이후 안구 건조 증상(SPEED, OSDI)과 안구 표면 지표(BUT, Oxford scale), 마이봄샘 기능 지표(MGE, MGS)는 치료 2주 후와 1달 후에 치료 전에 비해 모두 유의한 호전이 있었다(p＜0.05). 또한 치료 전 증상이 심했던 군과 치료 전 마이봄샘기능 이상 정도가 심했던 군에서 치료 후 개선 정도가 컸다(p＜0.05). 치료 후 마이봄샘의 기능 개선 정도(MGE 변화량)는 안구 표면상태의 호전(BUT, Oxford scale 변화량)과 유의한 관계를 보였지만, 건조 증상의 개선(SPEED, OSDI 변화량)과는 유의한 관계가 없었다. 치료기간 동안 임상적으로 유의한 부작용은 관찰되지 않았다. 결론: 마이봄샘 기능 이상 환자에서 자동 온열 압박 치료 기기는 안전성 있게 마이봄샘 기능 이상 및 안구 건조증을 호전시켰으며, 특히 중등도 이하의 마이봄샘 기능 이상에서는 안구 건조 증상과 마이봄샘 기능 이상 정도가 심한 경우에서 더욱 효과적이었다. Purpose: To evaluate the effect and prognostic factors of automated thermodynamic treatment (thermal compression therapy device [KCL 1100®]) for Meibomian gland dysfunction (MGD). Methods: Patients (48 eyes of 24 subjects) with MGD were recruited for a prospective clinical trial. Patients received 15-minute treatments twice a day using the KCL 1100®. Severity of dry eye symptoms were evaluated using the Standard Patient Evaluation for Eye Dryness (SPEED) and Ocular Surface Disease Index (OSDI), and severity of Meibomian gland function was evaluated using the Meibomian gland expressibility (MGE), Meibomian gland secretion (MGS) score and lipid layer thickness measured by LipiView®. To evaluate ocular surface, we measured tear break-up time (BUT) and fluorescein corneal staining score (Oxford scale). Data were presented for baseline and at 2 weeks and 1 month post-treatment. Results: Dry eye symptom (SPEED, OSDI), Meibomian gland function (MGE, MGS), and ocular surface index (BUT, Oxford scale) of patients were significantly improved from baseline to 2 weeks (p < 0.05) and 1 month post-treatment (p < 0.05). In addition, patients with more severe dry eye symptom and Meibomian gland index at baseline examination achieved improvement in mild to moderate MGD (p < 0.05). Improvement of Meibomian gland function (MGE) was associated with improvement of ocular surface index (BUT, Oxford scale) (p < 0.05), but not with improvement of dry eye symptom (SPEED, OSDI) (p > 0.05). There were no significant adverse events during the treatment. Conclusions: KCL 1100® automated thermodynamic treatment is an effective and safe treatment for MGD. Additionally, KCL 1100® is more effective in patients with moderate dry eye symptom and MGD. KCI Citation Count: 1